Serodiversity and antimicrobial resistance profiles of detected salmonella on swine production chain in Chiang Mai and Lamphun, Thailand - Phacharaporn Boonkhot (2018)
Background: Foodborne illness is growing public health problem worldwide. Salmonella is recognized as a major cause of this problem. Salmonella serotyping is a phenotypic characteristics which provided useful epidemiological markers for primary discrimination. The emergence and spread of antimicrobial resistant of this pathogen have become a major public health concern. The objectives of this study were to determine Salmonella serotypes, and antimicrobial resistance profiles on swine production chain (Farm-to-slaughtering process) in Chiang Mai and Lamphun, Thailand. Materials, Methods & Results: A total of 300 Salmonella strains were randomly selected from isolates recovered in 2011-2013 in Chiang Mai and Lamphun, Thailand, including the isolates from fecal, lymph node, pest and environmental samples. Serotyping and antimicrobial susceptibility testing was performed by WHO National Salmonella and Shigella center (Thailand). Salmonella isolates were serotyped by agglutination tests with antisera (S&A Reagents Lab Ltd., Thailand) on the basis of somatic-O, as well as phase 1 and phase 2 flagellar antigens according to the Kauffmanne-White scheme. In addition, all serotyping Salmonella isolates were detected for antimicrobial susceptibility testing by using the disk diffusion method of the Clinical and Laboratory Standard Institute. Ten antimicrobial agents were determined. The data were collected and analyzed for descriptive statistical analysis by Epi Info ™7. Twenty-one Salmonella serotypes were detected in both farms and slaughterhouses. Salmonella Rissen is the highest frequency found in both farms and slaughterhouses (30.7% and 38.0%, respectively). Thirty three antimicrobial resistance patterns were demonstrated. There were including 10 common patterns isolated from pig farms and slaughterhouses. The highest frequency antimicrobial resistant pattern was "AMP, S, TE" (47 isolates, 15.7%) followed by "AMP, SXT, C, S, TE" (44 isolates, 14.7%) and "AMP, SXT, S, TE" (36 isolates, 12.0%). Considering in each antibiotic agent, the highest frequency found was ampicillin (83.33%) followed by tetracycline (75.67%) and streptomycin (64%). The resistance of ciprofloxacin and norfloxacin of Salmonella isolates were not observed. There were no statistical differences in numbers of Salmonella found in different sources in each antimicrobial agent except cefotaxime and sulfamethoxazole-trimethoprim. Finally, ciprofloxacin and norfloxacin resistant strains were not found in both farms and slaughterhouses. Resistance to amoxicillin- clavulanic acid was not observed in Salmonella strains isolated from slaughterhouses. Discussion: Salmonella Rissen was also the majority serotypes in this region. Contrasting with the study in Germany, S. Rissen was found few in pig farms and slaughterhouses. Almost 90% of Salmonella spp. tested were resisted to antimicrobial at least 1 drug and 72% were multi drug resistance. Even though, we could not conclude the contamination from farms to slaughterhouses linked to the common source, but this study indicated that antimicrobial resistance- Salmonella can contaminate any steps of pig production line. Good practices and hygiene should be implemented to minimize this problem. Nevertheless, molecular epidemiology could further confirm the linkage of the contamination. The studies of antimicrobial resistance gene and molecular epidemiology should be performed.